FACTORS ASSOCIATED WITH THE USE OF 360-DEGREE LASER RETINOPEXY DURING PRIMARY VITRECTOMY WITH OR WITHOUT SCLERAL BUCKLE FOR RHEGMATOGENOUS RETINAL DETACHMENT AND IMPACT ON SURGICAL OUTCOMES (PRO STUDY REPORT NUMBER 4). Issue 11 (November 2020) - Wang, Jay C.; Ryan, Edwin H.; Ryan, Claire; Kakulavarapu, Srividya; Mardis, Patrick J.; Rodriguez, Marianeli; Stefater, James A.; Forbes, Nora J.; Gupta, Omesh; Capone, Antonio; Emerson, Geoffrey G.; Joseph, Daniel P.; et al.
Abstract : Purpose: To determine factors associated with 360-degree laser retinopexy (360LR) during primary pars plana vitrectomy ± scleral buckle for rhegmatogenous retinal detachment (RRD) and its impact on surgical outcomes. Methods: This is a multicenter, retrospective, interventional study. Patients undergoing primary pars plana vitrectomy or primary pars plana vitrectomy + scleral buckle for noncomplex primary RRD in 2015 were evaluated. Primary outcomes were single surgery anatomical success (SSAS) and final anatomical success. Secondary outcomes included final logarithm of the minimum angle of resolution visual acuity, epiretinal membrane formation, cystoid macular edema development, and number of subsequent vitrectomies. Multivariate regressions were performed. Results: Two thousand two hundred and forty-eight surgeries by 61 surgeons were included; of which, 516 underwent 360LR. Younger age ( P = 0.01), more retinal breaks ( P = 0.01), more extensive RRD ( P < 0.001), and surgeon ID ( P < 0.001) were significantly associated with 360LR. No significant associations between 360LR and single surgery anatomical success ( P = 0.44), epiretinal membrane formation ( P = 0.14), cystoid macular edema development ( P = 0.28), or number of subsequent vitrectomies ( P = 0.41) were found. Controlling for case complexity, 360LR was significantly associated with lower final anatomical success ( P < 0.001) and worse final logarithm of the minimum angle of resolution visual acuity ( P < 0.001). Conclusion: Multiple factors influenced whether 360LR was performed during primary pars plana vitrectomy ± scleral buckle for RRD. However, 360LR was not associated with improved surgical outcomes, and in fact, it may be associated with poorer outcomes. Abstract : Supplemental Digital Content is Available in the Text.In this multicenter, retrospective, interventional study of 2, 248 pars plana vitrectomies with or without scleral buckle for primary rhegmatogenous retinal detachment, the intraoperative application of 360-degree laser retinopexy was not associated with improved single surgery anatomical success and may be associated with poorer final visual and anatomical outcomes.